Unusual location of a glomangioma: a case report - Roshini, A. P.; Bhat, Vivek; Ramesh, Rakesh; Y. K., Inchara (International Surgery Journal, 2018)
Glomangioma or glomus tumors are rare neoplasms of the glomus body, which are located in the stratum reticularis of the dermis throughout the body. With a female preponderance, 75% of them occur in the subungual region and present with non-specific pain as the main complaint. Extradigital glomus tumours are rare and present a diagnostic challenge, seen most commonly in males. We present a case of a 47-year-old male who presented with a painful swelling in the forearm. MRI showed a hypodense lesion in the subcutaneous plane. After a wide local excision, histopathology revealed sheets of round cells with intervening vascular channels, characteristic of a glomus tumor.